ANALYSIS OF RIGID PAVEMENT STRUCTURAL DESIGN FOR AIRFIELD BASED ON THE ICAO METHOD - FIBRYANTO (NIM: 25002093); Pembimbing: Dr. Ir. Djunaedi Kosasih, M.Sc. dan Ir. Pamudji Widodo, ARIE
There are several design methods currently known for airfield rigid pavement structures, such as ICAO method (International Civil Aviation Organization), FAA method (Federal Aviation method) and PCA method (Portland Cement Association). These design methods calculate mixed aircraft traffic for design differently. The ICAO and the PCA methods are supported with a computer program which are available in the Highway Engineering Laboratorium of ITB. It offers a systematic approach for designers to carry out analysis and choose an effective design in accordance with conditions. In hand the ICAO method and the FAA method use load equivalent factor of each aircraft against the design aircraft, whereas the PCA methods takes into account rigid pavement wear age caused by each aircraft. The purpose of this research is to study a design approach based on design aircraft and mixed airraft. For this purpose sample data of aircraft flight and data of rigid pavement structure of the apron at Juanda airfield, Surabaya, are used. The research conducted is meant not for redesigning so that the assumtion taken in process analysis is the typical existing pavement thickness. Design process is implemented either manually based on the available design curve, in particular for a certain number of aircraft in common use, or by using a computer program (Airfield program). The result analysis of the three rigid pavement structure designs yields the same design aircraft, namely the A-330 aircraft. This due to the fact that the flexural stress in the rigid pavement structure due to the A-330 aircraft is the largest, namely 2.468 MPa. However, in the matter of safety factor, the three design methods differ. The safety factors for each method, the ICAO, PCA, and FAA, are respectively 1.20, 1.36, and 1.13. The safety factors differ, because of the difference in assumption used. For design approachs the design aircraft is used, every type of aircraft operating is assumed to be different conforming to each respective wheel configuration. Further results of analysis concerning design factor sensitivity on pavement thickness design (Ddesign), like the number of annual aircraft departures, aircraft characteristics, concrete flexural strength, and subgrade stability, very much influence pavement structure design, namely in the range of 0.01 till 0.75 (% change in Ddesign / % change in design data) in change design data in the amount of 20 %.